(untitled) (Annals of Medical Research, 2021)
Aim: It was targeted to calculate unit cost of reusable and disposable surgical drape sets using benefit/cost analysis and to determine how much these sets cost for the general hospital budget. Materials and Methods: The study was carried out in Inonu University Turgut Ozal Medical Center in Malatya city center, Turkey. In the study, a total of 500 packages and each package contain 7 drapes, 6 towels and 4 gowns. The packages, half of which are reusable and half of which are disposable and shared equally. Cost evaluation; it was obtained by calculating the purchase and waste disposal costs for disposable drapes. For reusable drapes, sewing, sterilization, washing, labor and waste disposal costs are calculated one by one. Afterwards, the total of costs obtained was analyzed and compared separately. Results: As a result of the analysis, it was found that the cost of reusable surgical drapes were cheaper than disposable drapes, and using reusable surgical drapes could provide a 33.74% saving in overall annual cost for hospital budget. Conclusion: Based on the novel findings; it is thought that by using reusable gowns and drapes can be contributed to the hospital’s budget.